Super-Additive Cooperation - Charles Efferson; Helen Bernhard; Urs Fischbacher; Ernst Fehr (Center for Economic Studies and ifo Institute (CESifo), 2022)
Repeated interactions provide a prominent but paradoxical hypothesis for human cooperation in one-shot interactions. Intergroup competitions provide a different hypothesis that is intuitively appealing but heterodox. We show that neither mechanism reliably supports the evolution of cooperation when actions vary continuously. Ambiguous reciprocity, a strategy generally ruled out in models of reciprocal altruism, completely undermines cooperation under repeated interactions, which challenges repeated interactions as a stand-alone explanation for cooperation in both repeated and one-shot settings. Intergroup competitions do not reliably support cooperation because groups tend to be similar under relevant conditions. Moreover, even if groups vary, cooperative groups may lose competitions for several reasons. Although repeated interactions and group competitions do not support cooperation by themselves, combining them often triggers powerful synergies because group competitions can stabilise cooperative strategies against the corrosive effect of ambiguous reciprocity. Evolved strategies often consist of cooperative reciprocity with ingroup partners and uncooperative reciprocity with outgroup partners. Results from a one-shot behavioural experiment in Papua New Guinea fit exactly this pattern. They thus indicate neither an evolutionary history of repeated interactions without group competition nor a history of group competition without repeated interactions. Our results are only consistent with social motives that evolved under the joint influence of both mechanisms together.
Keywords: C60; C70; C90; 330; evolution of cooperation; reciprocity; intergroup competition; social dilemma